Delving Deep Techniques We Wished We Had Known As Emerging Scholars - O'Kane, Paula (Research Methodology in Strategy and Management Series, 2024)
This volume answers questions such as what do researchers want to know more about? What is innovative and emerging that will change research in the future? What techniques are often overlooked that could open the door to new research questions or provide a more robust test of familiar questions?